COVID-19 vaccination and the skin to deltoid muscle distance in adults with diabetes. (April 2023) - Doppen, Marjan; Mirjalili, Ali; Harwood, Matire; Eathorne, Allie; Braithwaite, Irene; Bong, Jonathan; Kirton, Louis; Semprini, Ruth; Weatherall, Mark; Semprini, Alex; Kearns, Ciléin; Black, Melissa; et al.
Abstract: Objectives: To estimate the proportion of adult diabetics with a skin to deltoid muscle distance (SDMD) of > 25 mm, representing a distance greater than the standard needle length used for intramuscular COVID-19 vaccination, and to assess whether anthropometric measurements predict ultrasound SDMD measurements. Design: Non-interventional cross-sectional study. Setting: Single site, non-clinical setting, Wellington, New Zealand. Participants: One hundred participants (50 females) aged at least 18 years diagnosis with diabetes. All participants completed the study. Main outcome measures: The proportions of participants with a SDMD > 25 mm and a SDMD > 20 mm (indicating that the needle would not have penetrated at least 5 mm into the deltoid, which is considered necessary to ensure deposition of vaccine into muscle); the relationship between anthropometric measurements (body weight, body height, body mass index (BMI), skinfold thickness, arm circumference) and SDMD measured by ultrasound. Results: The proportion (95 % CI) of participants with a SDMD > 25 mm was 6/100; 6 % (2.2 to 12.6), and the proportion with a SDMD > 20 mm was 11 % (5.6 to 18.8), of which 9/11 had a BMI ≥ 30 kg/m 2 and 9/11 were female. The strongest relationships between anthropometric measurements and SDMD were with arm circumference (r = 0.76, P < 0.001) and BMI (r = 0.73, P < 0.001). Arm circumference and BMI were the best predictors of SDMD measurements with AUC for ROC curves of 0.99 and 0.94 above the 25 mm cut point, 0.97 and 0.89 above the 20 mm cut point respectively. Conclusions: The standard needle length of 25 mm is likely to be insufficient to ensure deposition of COVID-19 vaccine within the deltoid muscle in a small but important proportion of obese adults with diabetes. Arm circumference and BMI are simple measurements that could identify those that need a long needle to ensure successful intramuscular vaccine administration. Funding: Ruth Maud Ring Spencer Estate; Health Research Council of New Zealand (Independent Research Organisation).